Low Water-Demanding Binder Properties on Base Angren Residual Ash - Kh., Yusupov; Jalol, Abdukarimov (European Journal of Life Safety and Stability (2660-9630), 2022)
Analysis of experimental studies shows that the application of mechanical and chemical principles and the effect of a highly effective mechanism of action of chemical additives, first of all, the use of finely divided active mineral additives and super plasticizers, the emergence of types of binders, low-temperature application, when obtaining cement composite technology, such characteristics like high density, durability, uniformity, are the latest research papers that are missing. Scientific experimental data have shown that the activity of modern super plasticizers and additives of residual ash (dune sand) during the joint crushing of Portland cement clinker and gypsum stone under normal conditions on the 28th day of hardening is up to 69 MPa (when using dune sand) and 87 MPa (using residual ash) that a binder can be obtained.